Influence of Ca-doping on the nonlinear properties of novel ZnO-Cr2O3-based varistor ceramics. Issue 5 (May 2022) - Tian, Tian; Zheng, Liaoying; Podlogar, Mateja; Man, Zhenyong; Ruan, Xuezheng; Shi, Xue; Bernik, Slavko; Li, Guorong
Abstract: The influence of Ca-doping on the microstructure development and electrical characteristics was studied in the novel, ZnO-Cr2 O3 -based, varistor ceramics with the nominal composition (99.47-x) mol% ZnO + 0.1 mol% Cr2 O3 + 0.33 mol% Co3 O4 + 0.1 mol% La2 O3 + x mol% CaCO3, with x ranging from 0 to 6, sintered at 1200 °C. The results showed that, within the limits of the solid solubility of CaO in ZnO, the addition of CaO greatly enhanced the diffusion processes and hence the grain growth, thus broaden the range of breakdown voltages. Moreover, the Ca-doping simultaneously increases the height of the electrostatic Schottky barrier, resulting in a higher nonlinear coefficient of 40 and a lower leakage current of 2.8 μA/cm 2 . The results are important for the potential application of these novel ZnO-Cr2 O3 -based varistors, having different nominal voltages and yet suitable dimensions, in overvoltage protection across a broad range of voltages.